Border [videorecording (DVD)] - Burgard, Christopher (BorderMovie.com ; Passion River], 2008)
"An investigative documentary on the state of our southern border with Mexico. Dissatisfied with second-hand media coverage, Burgard and his camera team journeyed down to the U.S. Mexican border and, over a period of several months, interviewed Border Patrol agents, illegal immigrants, Minutemen, politicians, representatives of the ACLU and local ranchers to make a realistic assessment of just how porous our border had become"--Film website.